Writing After the Horror: The Dislocated Time in Kurt Vonnegut's Novel "Slaughterhouse Five" - Hernández García, María Luisa (Tropelías: Review of Literary Theory and Comparative Literature, 2023)
Faced with the difficulty of expressing the horror, Kurt Vonnegut in the novel Slaughterhouse Five, with a simple language and a rhythm that transmits calm, resorts, among other strategies such as the deployment of a dense network of intertexts or the insertion of appeasing drawings, to the fragmentation and dislocation of time, present not only in the plot of the novel, in which it is seen as a block of moments, but also in its discursive configuration; thus achieving a vivid anti-war picture, at once tender and humorous, inserted in a scenario in which autofiction, historical realism, social criticism and science fiction are harmoniously combined.
Keywords: Vonnegut; Time; Fictional Worlds; Intertextuality; Autofiction; Science Fiction